Unveiling the Potential and Significance of Marketing Research in the Nigerian Banking Industry - Oshireku Vincent Onivefu; Omuya Stephen Onivefu; Adaviriku John Onivefu; Zainab Oyioza Onivefu; Oziofu Blessing Onivefu; Abosede Mary Latinwo (Emerging Markets Journal)
This research aims to assess the significance of marketing research within the Nigerian banking sector. The study pursues the following objectives: First, to appraise the potential of marketing research as a gauge for a firm's advancement; second, to examine if marketing research contributes to a firm's economic viability; and third, to ascertain the extent of customer satisfaction achievable through marketing research. The research employed a combined descriptive and explanatory design. Data were collected through questionnaires and supplemented by library research. Both primary and secondary data sources were utilized, and data analysis employed the chi-square statistical method at a 5% significance level. The results were presented in frequency tables and percentages. The participants in the study consisted of 67 employees from the Union Bank of Nigeria Benin branch. The central focus of this research was to highlight the significance of marketing research within the Nigerian banking sector. The findings of the study revealed that the disregard for marketing research has precipitated the premature closure of banks in the industry. Moreover, the study demonstrated that marketing research holds the potential to enhance and cultivate the banking sector. In light of these findings, it is recommended that banks should proactively engage in marketing research to foster the growth and development of the banking industry.